2012
DOI: 10.2136/vzj2011.0088
|View full text |Cite
|
Sign up to set email alerts
|

Using Dye Tracer for Visualization of Preferential Flow at Macro‐ and Microscales

Abstract: The detection of a nonequilibrium water flow and solute transport in structured soil at various scales is essential for better understanding of these phenomena. This study focused on the visualization of preferential flow in a Haplic Luvisol and Haplic Cambisol and their horizons by performing field ponding dye infiltration experiments. In addition, thin soil sections were made and micromorphological images were used to study soil aggregate structure and dye distribution at the microscale. The staining pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 66 publications
0
42
1
Order By: Relevance
“…However, larger WDPT values measured at surfaces with coatings than those at uncoated surface were also associated with generally lower hydraulic conductivity of coatings (consisted of fine grained material) in comparison to hydraulic conductivity of aggregate interiors. Considerable differences between the hydraulic conductivities of aggregate coating and interiors were observed for soil aggregates taken from the same soil horizon by Fér and Kodešová (2012) and Kodešová et al (2012). Results of our measurements on dry soil samples showed a slightly different relationship between WDPT and PWI, than those results of Leue et al (2015), who observed a non-linear relationship between PWI and WDPT (R = 0.5, p < 0.001) for different types of preferential flow path surfaces.…”
Section: Wdpt Explained By Pwi Of Som At Aggregate Surfacescontrasting
confidence: 66%
See 2 more Smart Citations
“…However, larger WDPT values measured at surfaces with coatings than those at uncoated surface were also associated with generally lower hydraulic conductivity of coatings (consisted of fine grained material) in comparison to hydraulic conductivity of aggregate interiors. Considerable differences between the hydraulic conductivities of aggregate coating and interiors were observed for soil aggregates taken from the same soil horizon by Fér and Kodešová (2012) and Kodešová et al (2012). Results of our measurements on dry soil samples showed a slightly different relationship between WDPT and PWI, than those results of Leue et al (2015), who observed a non-linear relationship between PWI and WDPT (R = 0.5, p < 0.001) for different types of preferential flow path surfaces.…”
Section: Wdpt Explained By Pwi Of Som At Aggregate Surfacescontrasting
confidence: 66%
“…Aggregate coatings and biopore walls are characteristic soil structural features (e.g., Gerke and Köhne, 2002;Kodešová, 2009;Kodešová et al, 2011Kodešová et al, , 2015Rogasik et al, 2014) that are of great importance when attempting to describe preferential flow and transport processes in soils (e.g., Gerke, 2012;Kodešová, 2009;Kodešová et al, 2008Kodešová et al, , 2009Kodešová et al, , 2010Kodešová et al, , 2012. Clay-organic coatings often cover aggregates and biopores in the clay-illuviation Bt-horizons of Luvisols (IUSS Working Group WRB, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roots' volume may have varied due to their water content oscillation, which corresponded to the soil water content changes (Hillel 1998). Thus a preferential pathway could be created along the roots (Köhne et al 2009;Kodešová et al 2011Kodešová et al , 2012b. In such case a dual-permeability model (Gerke and van Genuchten 1993) in HYDRUS-2D would be more suitable to approximate the observed data .…”
Section: Water Fluxmentioning
confidence: 99%
“…The flow pathways of water through field soils are highly irregular in many cases, as it was demonstrated by dye tracer infiltration experiments (e.g., Flury et al 1994;Dohnal et al 2009;Homolák et al 2009;Kodešová et al 2012). To quantify the heterogeneity of water flow in soils, Täumer et al (2006) proposed to use the effective cross section (ECS).…”
Section: Introductionmentioning
confidence: 99%